Answer:

Step-by-step explanation:
by factorising ;
=》

=》

=》

=》

<em>i</em><em> </em><em>hope</em><em> </em><em>it</em><em> </em><em>helped</em><em>.</em><em>.</em><em>.</em><em>.</em><em>.</em>
<span><span> x = -1/2 = -0.500
</span><span> x = 5/2 = 2.500
EITHER ONE WORKS</span></span>
1) To find the confidence interval
the sample mean x = 38 σ = 9; n = 85;
The confidence level is 95% (CL = 0.95) <span>CL = 0.95
so α = 1 – CL = 0.05
</span><span>α/2 = 0.025 </span>Z(α/2) = z0.025
The area to the right of Z0.025 is 0.025 and the area to the left of Z0.025 is 1 – 0.025 = 0.975
Z(α/2) = z0.025 = 1.645 This can be found using a computer, or using a probability table for the standard normal distribution.
<span>EBM = (1.645)*(9)/(85^0.5)=1.6058</span> x - EBM = 38 – 1.6058 = 36.3941 <span> x + EBM = 38 + 1.6058 = 39.6058
</span>The 95% confidence interval is (36.3941, 39.6058).
The answer is the letter D
<span>The value of 40.2 is <span>within the 95% confidence interval for the mean of the sample
</span></span>2) To find the confidence interval <span>
<span>the sample mean x = </span>76 σ = 20; n = 102; </span><span>
The confidence level is 95% (CL = 0.95) CL = 0.95
so α = 1 – CL = 0.05
α/2 = 0.025 Z(α/2) = z0.025
The area to the right of Z0.025 is 0.025 and the area to the
left of Z0.025 is 1 – 0.025 = 0.975
Z(α/2) = z0.025 = 1.645 This can be found using a computer,
or using a probability table for the standard normal distribution.
EBM = (1.645)*(20)/(102^0.5)=3.2575 x - EBM = 76 – 3.2575 = 72.7424 </span> x +
EBM = 76 + 3.2575 = 79.2575 <span>
The 95% confidence interval is (</span>72.7424 ,79.2575).<span>
The answer is the letter </span>A
and the letter D<span>
The value of 71.8 and 79.8 <span> are </span> outside<span>
the 95% confidence interval for the mean of the sample</span></span>
This the only option to find x since doing the other way like 3x + 2 = 3x + 2 gives it an infinite solution.
4x - 1 = 3x + 2
-3x -3x
1x - 1 = 2
+1 +1
1x = 3
--- ----
1 1
x = 3
Check:
4(3) - 1 = 3(3) + 2
12 - 1 = 9 + 2
11 = 11
The principal square root of 49 is just
7 because 7 times 7 is 49.
It can not be -7 because
a principle square root cannot be negative.
